2017
DOI: 10.1136/neurintsurg-2017-013308
|View full text |Cite
|
Sign up to set email alerts
|

Wall enhancement ratio and partial wall enhancement on MRI associated with the rupture of intracranial aneurysms

Abstract: ObjectivesTo evaluate the risk factors for rupture of intracranial aneurysms (IAs) using high resolution MRI (HRMRI).Methods91 consecutive patients with 106 IAs were reviewed from February 2016 to April 2017. Patients and IAs were divided into ruptured and unruptured groups. In addition to the clinical characteristics of the patients, the features of IAs (eg, shape) were evaluated by CT angiography, whereas wall thickness, enhanced patterns, and enhancement ratio (ER) were evaluated by MRI. Multiple logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 23 publications
1
49
0
1
Order By: Relevance
“…15 Concordantly, vessel wall assessment in three large cohorts with a total of 108 ruptured aneurysms and 302 unruptured aneurysms showed a correlation between enhancement of the aneurysm wall and rupture status. 17,18,24 One of these studies reported that partial wall enhancement was solely observed at irregular regions and daughter sacs of aneurysms. 24 Because aneurysm irregularity has been related to rupture status, some have hypothesized that endothelial damage and inflammation are the likely causes of aneurysm enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Concordantly, vessel wall assessment in three large cohorts with a total of 108 ruptured aneurysms and 302 unruptured aneurysms showed a correlation between enhancement of the aneurysm wall and rupture status. 17,18,24 One of these studies reported that partial wall enhancement was solely observed at irregular regions and daughter sacs of aneurysms. 24 Because aneurysm irregularity has been related to rupture status, some have hypothesized that endothelial damage and inflammation are the likely causes of aneurysm enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,24 One of these studies reported that partial wall enhancement was solely observed at irregular regions and daughter sacs of aneurysms. 24 Because aneurysm irregularity has been related to rupture status, some have hypothesized that endothelial damage and inflammation are the likely causes of aneurysm enhancement. 10 However, these irregular regions and daughter sacs are very susceptible to different, much slower flow patterns, which may lead to insufficient flow suppression within the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…VWI of aneurysm walls has demonstrated increased enhancement in growing and recently ruptured aneurysms. 23,30,45,67 VWCE has been correlated with inflammatory changes at a histological level, 57 and has been associated with inflammatory vasculopathies such as mycotic aneurysms and HIV-associated vasculitis. 28 Multiple Cerebral Aneurysms.…”
Section: Cerebral Aneurysmsmentioning
confidence: 99%
“…After the initial report by Matouk et al, 34 subsequent studies have examined more than 500 aneurysms and found that > 95% of ruptured aneurysms demonstrated enhancement. 17,25,42,45,64,67 Approximately 25% of unruptured aneurysms also demonstrated enhancement; many of them were deemed unstable based on documented growth or symptoms. These results suggest that VWI has a high sensitivity and negative predictive value for identifying acute ruptured aneurysms.…”
Section: Cerebral Aneurysmsmentioning
confidence: 99%
“…Wang et al reported their evaluation of 106 intracranial aneurysms utilizing high resolution MRI (HRMRI) 8. The authors determined that those aneurysms with an enhancement ratio of ≥61.5% and evidence of peripheral wall enhancement were more frequently associated with rupture.…”
mentioning
confidence: 99%